21.8k views
0 votes
Solve for u.

4u = 16u + 3(–3u − 5)

u =

2 Answers

0 votes

Answer:


\boxed{u = 5}

Explanation:


= > 4u = 16u + 3( - 3u - 5) \\ \\ = > 4u = 16u + (3 * ( - 3u)) - (3 * 5) \\ \\ = > 4u = 16u - 9u - 15 \\ \\ = > 4u = 7u - 15 \\ \\ = > 4u - 7u = - 15 \\ \\ = > \cancel{- }3u = \cancel{- }15 \\ \\ = > 3u = 15 \\ \\ = > u = (15)/(3) \\ \\ = > u = 5

User Lam Le
by
5.3k points
0 votes

Answer:

u = 5

Explanation:

→Distribute the 3 to (-3u - 5):

4u = 16u - 9u - 15

→Add like terms:

4u = 7u - 15

→Subtract 4u from both sides:

0 = 3u - 15

→Add 15 to both sides:

15 = 3u

→Divide both sides by 3:

5 = u

User Pabigot
by
5.1k points